Relationship Relationship Between Income and Food Quality of the Population of the Republic of Kazakhstan - A. I. Gizzatova; S. M. Yessengaliyeva; A. M. Kazambaeva (Экономика: стратегия и практика)
The purpose of the article is to study the relationship between the income level and the quality of nutrition of the population of the republic, per capita consumption of basic foodstuffs by population groups with different disposable incomes, the main problems, and ways to solve them. The main source of information was the official data of the Bureau of National Statistics of the Agency for Strategic Planning and Reforms of the Republic of Kazakhstan. The theoretical basis of the research was the works of domestic and foreign scientists in the field of the level and quality of life, materials of the FAO. The study was conducted using general scientific methods of cognition, as well as special methods of economic and statistical analysis - grouping, graphical research method, ranking of the dynamic series, calculated indicators of the analysis of dynamic series. The scientific novelty of the study is to assess the impact of changes in disposable income on the concentration and differentiation of income of the population, food consumption in different income groups of the population of the republic. The authors analyzed the main modern concepts of measuring the standard of living and selected the most acceptable information from the point of view of accessibility, which was the basis of the study. The results of the study can be used in the formation of medium- and long-term programs to increase the income and quality of nutrition of the population, as well as a basis for further research in this direction.